1991
DOI: 10.1080/02640419108729850
|View full text |Cite
|
Sign up to set email alerts
|

Maximal exercise performance and lean leg volume in men and women

Abstract: The purpose of this study was to compare the maximal exercise performance during cycle ergometry of 34 men and 47 women. External peak power output (OPP) and optimized pedalling rate (ORPM) were calculated from data gathered during an optimization procedure performed on a friction braked cycle ergometer. In addition, lean leg volume (LLV) and lean upper leg volume (LULV) were determined using an anthropometric technique. Both OPP and ORPM were greater in men than in women (1007 +/- 135 vs 673 +/- 109 W and 119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…Both the loss of muscle mass and oxidative potential appear to be important determinants of aerobic power in this older age range. Other investigations using either a linear adjustment model to normalise ýOµ,max for lean leg volumes (Winter et al 1991) and FFM (Toth et al 1993), or a log-linear adjustment model that incorporated leg strength (Neder et al 1999), have demonstrated a similar elimination of differences between the sexes. The importance of the functional capacity of the muscle was demonstrated in this latter study since leg strength, but not lean muscle mass, abolished sex differences in the agerelated decline in ýOµ,max.…”
Section: ----------------------------mentioning
confidence: 89%
See 1 more Smart Citation
“…Both the loss of muscle mass and oxidative potential appear to be important determinants of aerobic power in this older age range. Other investigations using either a linear adjustment model to normalise ýOµ,max for lean leg volumes (Winter et al 1991) and FFM (Toth et al 1993), or a log-linear adjustment model that incorporated leg strength (Neder et al 1999), have demonstrated a similar elimination of differences between the sexes. The importance of the functional capacity of the muscle was demonstrated in this latter study since leg strength, but not lean muscle mass, abolished sex differences in the agerelated decline in ýOµ,max.…”
Section: ----------------------------mentioning
confidence: 89%
“…The reduction of aerobic power with advancing age might be either a consequence of the loss of cardiovascular function (Hossack & Bruce, 1982;Hagberg et al 1985;Lakatta, 1993;Petrella et al 1994) or the loss of muscle mass (Fleg & Lakatta, 1988;Winter et al 1991;Toth et al 1993;Jackson et al 1995;Johnson et al 2000). In order to study this question we extended our previous analyses of the data based on 146 women and 152 men, between 55 and 86 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high correlation has been consistently found between isometric muscle strength and muscle cross-sectional area (CSA; Ikai and Fukunaga 1968;Maughan et al 1983;Maughan and Nimmo 1984;Davies 1985). Winter et al (1991) observed a high correlation between the peak power of maximal exercise and lean leg volume for cycle ergometry in humans. Recently it has been reported that accumulated peak O 2 -deficit may be influenced by the muscle volume (Sloniger et al 1997).…”
Section: Introductionmentioning
confidence: 90%
“…Winter et al 1991;EsbjoÈ rnsson et al 1993). Furthermore, the accumulation of blood and muscle lactate and of plasma ammonia has been shown to be lower in females following sprint exercise (Jacobs et al 1983;Itoh and Ohkowa 1993;Gratas-Delamarche et al 1994 ;Nevill et al 1996).…”
Section: Introductionmentioning
confidence: 99%